Tinjauan Hukum Distribusi Pupuk Bersubsidi pada Aspek Hukum Pidana - Usman Iman Usman; Endang Sutrisno (Institut Agama Islam Nasional Laa Roiba Bogor, 2026)
The agricultural sector is crucial for national food security, with subsidized fertilizer serving as an instrument to maintain farmers' purchasing power. However, its distribution often faces challenges in the form of price fluctuations above the HET (Highest Retail Price) and leakage into the non-subsidized sector. In response, the government issued Presidential Regulation No. 6 of 2025 in conjunction with Presidential Regulation No. 113 of 2025 to tighten supervision. This study aims to analyze the legal construction of this governance and its implications for economic criminal law. The method used is a doctrinal-normative juridical analysis with descriptive analysis. Primary legal sources are Presidential Regulation No. 6 of 2025 and Law No. 7 of 2014 concerning Trade, while secondary sources are from scientific literature. Data were collected through a literature review and structured field observations. The results show that Presidential Regulation No. 6 of 2025 strengthens the digitalization of real-time monitoring systems to facilitate criminal evidence. This regulation establishes layered sanctions, including administrative sanctions, imprisonment/fines via the Trade Law, and Emergency Law No. 7 of 1955 as an anchor for economic crimes. Law enforcement continues to prioritize the principle of ultimum remedium, which prioritizes criminal sanctions for substantive malicious intent (mens rea), while strengthening corporate responsibility and the function of the KP3 (Commission for Supervision and Protection of Food and Agriculture). In conclusion, distribution irregularities at the distributor and retailer levels are systematic, harming farmers. Implementing an integrated distribution scheme and consistent law enforcement are essential prerequisites for legal certainty and equitable food sovereignty.